THE EFFECTIVE WAYS OF ORGANIZATION OF INNOVATIVE PROCESSES AT SECONDARY SCHOOLS - Sokhiba Ibragimovna Mirkhayitova; Bakhtiyor Umidovich Aminov; Osiyokhon Karimova (Galaxy International Interdisciplinary Research Journal, 2023)
The article represents general secondary school education, ensuring efficiency as an integral pedagogical system interconnected with innovative processes to increase the effectiveness of learning and learning processes in the organization and management of innovative processes